2010
DOI: 10.1007/s11199-010-9790-6
|View full text |Cite
|
Sign up to set email alerts
|

Daring to Be Darling: Attractiveness of Risk Takers as Partners in Long- and Short-Term Sexual Relationships

Abstract: In an attempt to explain gender differences in risk taking from an evolutionary perspective, this study examined the attractiveness of risk taking in potential mates. Questionnaire data from a sample of 352 primarily undergraduate students at Liverpool University, U.K., provided participants' ratings of physical, social and financial risk-taking and risk-avoiding profiles in terms of attractiveness for long-and short-term relationships. As well as showing a considerable variation in the ratings of different ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
49
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 60 publications
3
49
0
Order By: Relevance
“…In another study, Vincke (2017) revealed the existence of a moderate correlation between binge drinking and the level of sexual unrestrictedness (i.e., higher sociosexual orientation score and short-term mating orientation) confirming that the signaler is sexually shortterm oriented. These studies confirm the general differences in risk-taking perception between risk avoiders (attractive for long-term mating) and risk takers (attractive only for shortterm mating, see Sylwester & Pawłowski, 2011).…”
supporting
confidence: 79%
“…In another study, Vincke (2017) revealed the existence of a moderate correlation between binge drinking and the level of sexual unrestrictedness (i.e., higher sociosexual orientation score and short-term mating orientation) confirming that the signaler is sexually shortterm oriented. These studies confirm the general differences in risk-taking perception between risk avoiders (attractive for long-term mating) and risk takers (attractive only for shortterm mating, see Sylwester & Pawłowski, 2011).…”
supporting
confidence: 79%
“…situations, studies demonstrated that physical risk taking is especially attractive in short-term mating contexts (Bassett & Moss, 2004;Kelly & Dunbar, 2001;Sylwester & Pawłowski, 2011). Consequently, in this article, we aim to explore the hypothesis that male smoking and drinking behavior-being risky physical consumption behaviors-are used as a male short-term mating strategy.…”
mentioning
confidence: 98%
“…This is because people of a lower socio‐economic background are more prone to engage in risk‐taking and impulsive activities (Griskevicius, Tybur, Delton, & Robertson, ) and they also have a higher incidence of alexithymia (Lane, Sechrest, & Riedel, ) and poor academic outcomes (see Sirin, , for a review). Risk‐taking often leads to short‐term gains such as dominance in social hierarchies and increased attractiveness to potential mates (Sylwester & Pawlowski, ). For adolescents who have limited socio‐economic resources, engaging in such risk‐taking activities allows them to increase their status in a way that is adaptive in their unstable environment (Griskevicius et al, ).…”
Section: Discussionmentioning
confidence: 99%